Towards outstanding achievement in management & administration of examplary religious school: case study among principals in Tutong, Brunei - Zakaria, Gamal Abdul Nasir (Universiti Teknologi Malaysia, 2018)
The purpose of this study is to identify the principals’ management and administration level and to discover the difficulties in management and administration encountered by the school authorities in the effort to qualify in achieving the exemplary school tittle among religious school in Tutong district, Brunei. 10 principals from the participating religious school were interviewed to collect comprehensive information. The data was then analyzed by using SPSS software to attain frequency, percentage and min score. Finding shows that the management level of religious school is in satisfactory level. The study also recognizes that there are a few difficulties that were encountered by the administers in the effort to achieve the exemplary school title. At the end of the study, a few suggestions were made to ensure that the management and administration process are performed more smoothly and thus will successfully achieve exemplary religious school title.